Inequalities in Educational Outcomes: How Important Is the Family? - Julia Bredtmann; Nina Smith (Institute for the Study of Labor (IZA), 2016)
In this paper, we investigate sibling correlations in educational outcomes, which serve as a broad measure of the importance of family and community background. Making use of rich longitudinal survey and register data for Denmark, our main aim is to identify the parental background characteristics that are able to explain the resemblance in educational outcomes among siblings. We find sibling correlations in educational outcomes in the range of 15 to 33 percent, suggesting that up to a third of the variation in educational achievement can be explained by family and community background. Our results further reveal that parents' socio-economic background can account for a large part of the sibling correlation. Other family characteristics such as family structure, the incidence of social problems, and parents' educational preferences also play a role, though these factors only contribute to explaining sibling similarities at lower levels of the educational distribution.
Keywords: I21; I24; J13; 330; intergenerational mobility; sibling correlations; education